Behavioural responses to a wealth tax. (25th October 2021) - Advani, Arun; Tarrant, Hannah
Abstract: In this paper, we review the existing empirical evidence on how individuals respond to the incentives created by a net wealth tax. Variation in the overall magnitude of behavioural responses is substantial: estimates of the elasticity of taxable wealth vary by a factor of 800. We explore three key reasons for this variation: tax design, context and methodology. We then discuss what is known about the importance of individual margins of response and how these interact with policy choices. Finally, we use our analysis to systematically narrow down and reconcile the range of elasticity estimates. We argue that a well‐designed wealth tax would reduce the tax base by 7–17 per cent if levied at a tax rate of 1 per cent.